PERENCANAAN SISTEM MANAJEMEN K3 FAKULTAS TEKNIK UPN “VETERAN” JAWA TIMUR - Gilang Nur Dwi Setiawan; Euis Nurul Hidayah (Envirotek : Jurnal Ilmiah Teknik Lingkungan, 2021)
The Faculty of Engineering, UPN "Veteran" East Java, has a total workforce of 100 people, who work in the laboratory and outside the laboratory. According to Per-05 / MEN / 1996 in chapter III article 3, it states that a workplace containing 100 people or more contains potential hazards that can lead to work accidents. To create a higher education institution that has safety, it is necessary to plan an K3 Management System which is used as a reference or guideline for the Faculty of Engineering UPN "Veteran" East Java. The drafting and its application were carried out by observing the work process and identifying hazards in each laboratory at the Faculty of Engineering. Based on the results of data processing and analysis, it can be concluded that the types of hazards that have a high risk value level of 49, a moderate risk value level of 19, and a low risk value level of 38, this is not acceptable and should require training.